STAGE OF FORMATION AND DEVELOPMENT OF LINGUCULTUROLOGY AS A SCIENCE - Xotamova Lobar Shukrulloyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ABSTRACT. This article discusses lingua-cult urology, a modern branch of linguistics. An analysis of the field of study of lingua-culturology is given.